High Intensity Aerobic Interval Training Improves Peak Oxygen Consumption in Patients with Metabolic Syndrome: Cat [el Entrenamiento Aeróbico de Intervalo de Alta Intensidad Mejora el Consumo de Oxígeno Peak en Pacientes Con Síndrome Metabólico: Cat] - Cofre-Bolados, C (2014)
CONCLUSION: In spite of the methodological shortcomings of the primary studies included in the systematic review, we reasonably conclude that implementation of high intensity aerobic interval training in subjects with metabolic syndrome, leads to increases in peak oxygen consumption.INTRODUCTION: A number of cardiovascular risk factors characterizes the metabolic syndrome: insulin resistance (IR), low HDL cholesterol and high triglycerides. The aforementioned risk factors lead to elevated levels of abdominal adipose tissue, resulting in oxygen consumption deficiency.PURPOSE: To verify the validity and applicability of using high intensity interval training (HIIT) in subjects with metabolic syndrome and to answer the following question: Can HIIT improve peak oxygen consumption?METHOD: The systematic review "Effects of aerobic interval training on exercise capacity and metabolic risk factors in individuals with cardiometabolic disorders" was analyzed.RESULTS: Data suggests high intensity aerobic interval training increases peak oxygen consumption by a standardized mean difference of 3.60 mL/kg-1/min-1 (95% confidence interval, 0.28-4.91).Abstract available from the publisher.